Russian Federation : 2018 Article IV Consultation-Press Release; Staff Report; Informational Annex; Supplementary Information. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2018)
The Russian economy is recovering from the 2015-16 recession. Over the past few years, the authorities have put in place a strong macroeconomic policy framework that has reduced uncertainty and helped weather external shocks. However, Russia's convergence to advanced economy income levels has stalled and its weight in the global economy is shrinking.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet